Enhancing Teachers' Skills, Social Studies Learning, and Students' Outcomes Through Book Creator and the ADDIE Model - Fitria, Isna; Sumanti, Sumanti; Marisa, Riandi (International Journal of Educational Dynamics, 2024)
This study aims to improve teachers' skills in creating teaching media, enhance the quality of social studies learning, and boost students' learning outcomes by utilizing Book Creator as a teaching medium within the ADDIE framework. The R&D method was employed, guided by the ADDIE model. The media was validated by experts in material, language, and media design, and then implemented with sixth-grade students in a real classroom setting. Practicality and effectiveness were assessed using teacher and student feedback questionnaires. The findings demonstrated significant improvements in teachers' ability to design effective teaching materials, with high validation scores from experts. Social studies learning quality was enhanced through interactive features, fostering student engagement and critical thinking. Teachers and students rated the practicality of the teaching media highly, scoring 83% and 81%, respectively. Additionally, students' academic performance improved markedly, with average scores increasing from 68 ("sufficient") to 82 ("good"). The ADDIE framework enabled systematic development and iterative refinement, ensuring alignment with pedagogical goals. This study highlights the potential of combining structured instructional design models like ADDIE with innovative digital tools to improve educational outcomes. The studies provide a robust foundation for broader application in various subjects and educational contexts.